2020
DOI: 10.3390/genes11020172
|View full text |Cite
|
Sign up to set email alerts
|

Altered miRNA and mRNA Expression in Sika Deer Skeletal Muscle with Age

Abstract: Studies of the gene and miRNA expression profiles associated with the postnatal late growth, development, and aging of skeletal muscle are lacking in sika deer. To understand the molecular mechanisms of the growth and development of sika deer skeletal muscle, we used de novo RNA sequencing (RNA-seq) and microRNA sequencing (miRNA-seq) analyses to determine the differentially expressed (DE) unigenes and miRNAs from skeletal muscle tissues at 1, 3, 5, and 10 years in sika deer. A total of 51,716 unigenes, 171 kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 74 publications
2
14
0
Order By: Relevance
“…In this study, 3 male red deer were selected to collect antler samples at about 30 d, 60 d and 90 d growth stages, so that there were 3 samples from different individuals at each time point. In high-throughput sequencing, every sample pool was a mix of equal amount of RNAs from three individual male deer, as was the case in other studies [ 7 , 40 , 41 , 42 ], which indicated that this method was acceptable. However, studies with at least biological replicates may be more meaningful and acceptable compared with RNA pools, though each pool is collected with at least three samples.…”
Section: Discussionmentioning
confidence: 91%
“…In this study, 3 male red deer were selected to collect antler samples at about 30 d, 60 d and 90 d growth stages, so that there were 3 samples from different individuals at each time point. In high-throughput sequencing, every sample pool was a mix of equal amount of RNAs from three individual male deer, as was the case in other studies [ 7 , 40 , 41 , 42 ], which indicated that this method was acceptable. However, studies with at least biological replicates may be more meaningful and acceptable compared with RNA pools, though each pool is collected with at least three samples.…”
Section: Discussionmentioning
confidence: 91%
“…And Zeng et al have reported the MYH1B has a crucial role in the development of thigh muscle rather than pectoral muscle in the immunocastration chicken model ( Zeng et al., 2020 ). Likewise, the MYH gene family has been shown to be similarly important in deer ( Jia et al, 2020 ), pig ( Fazarinc et al, 2020 ), and cattle ( Picard and Gagaoua, 2020 ). Consistent with previous studies, significantly enriched tight junction pathway is crucial to growth rate and myoblast differentiation in chickens ( He et al, 2020 ; Huang et al, 2020a ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that miR-127-5p directly targeted NAMPT , which promoted the viability of osteoarthritis chondrocytes and inhibited cell apoptosis, inflammation and extracellular matrix degradation ( 33 , 34 ). Jia et al researched and screened the differentially expressed miRNAs in skeletal muscle tissue of sika deer at 1, 3, 5 and 10 years old ( 35 ). Among them, miR-199a-5p might play a key role in muscle aging.…”
Section: Discussionmentioning
confidence: 99%